Pilot scale separation of CO2 from power plant flue gases by membrane technology. (October 2016) - Pohlmann, Jan; Bram, Martin; Wilkner, Kai; Brinkmann, Torsten
Highlights: Membrane based CO2 removal from power plant flue gases. Long term operation of pilot plant. Stability of membrane material exposed to flue gas. Intermittent operation due to fluctuating electricity demand. Abstract: Removing carbon dioxide from power plant flue gases is an increasingly important separation task to limit the amount of greenhouse gases emitted to the atmosphere. In contrast to competing processes, membrane technology requires less time to react to changing feed conditions. Hence it is ideally suited to operate efficiently even under partial load and at irregular intervals. I.e. the scenarios conventional power plants are facing today due to the increasing amount of renewable energy supplied to the power grid. In this work the results of several experiments using a membrane gas separation pilot plant connected to a hard coal fired power plant are presented. Feed flowrate, temperature, dew point and composition as well as permeate pressure were varied during the experiments. The influences of these parameters on module performance, as well as the transition between different operating conditions were investigated. During these experiments the plant was frequently operated with ambient air during downtimes of the power plant. This allowed for a start-up and shut-down procedure to be developed, which is important to ensure the stability of the membrane. In order to gauge the stability of the process the experimental data is compared to a previously validated model.